Anatomy of the back: muscles and clinical anatomy - Matthan, Joanna (Henry Stewart Talks, 2025)
Muscles of the back, Spinotransversales muscles, Erector spinae muscles, Transversospinales muscles, Thoracic nerve, Spinal cord & spinal nerves, Arrangement of a spinal nerve, Associated vasculature in the interspinous foramina, Disc herniation (slipped disc’), Spinal deformities, Spondylolisthesis, Ankylosing spondylitis